2021
DOI: 10.1007/s12144-021-02016-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring loneliness and students’ sense of coherence (S-SoC) in the university setting

Abstract: Background. Loneliness is a prevalent global public health issue, and this topic is also common among university students. From a health-related, resource-oriented approach like the salutogenic model, loneliness can be interpreted as a potential stressor. To cope effectively with this stressor, a strong Sense of Coherence is needed to mobilize resources like social support. Interventions to promote health and wellbeing within a university setting should include a salutogenic focus. However, currently, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…Individuals with a disintegrated identity thus have more difficulty integrating positive and negative representations of self and others, which makes them less able to interact with others (Di Pierro et al, 2018) and makes them more prone to criminal behavior along with isolated narcissists (Bogaerts et al, 2021). Similarly, isolated narcissists may have a less integrated identity due to their increased need for social isolation (Chu et al, 2016;Limarutti et al, 2021). In brief, in addition to supporting existing findings, our study provides direct evidence that identity integration may explain why vulnerable and isolated narcissists have a lower capacity to relate to others than grandiose narcissists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with a disintegrated identity thus have more difficulty integrating positive and negative representations of self and others, which makes them less able to interact with others (Di Pierro et al, 2018) and makes them more prone to criminal behavior along with isolated narcissists (Bogaerts et al, 2021). Similarly, isolated narcissists may have a less integrated identity due to their increased need for social isolation (Chu et al, 2016;Limarutti et al, 2021). In brief, in addition to supporting existing findings, our study provides direct evidence that identity integration may explain why vulnerable and isolated narcissists have a lower capacity to relate to others than grandiose narcissists.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to isolated narcissism, there is no empirical evidence on how it relates to identity integration. However, a stronger sense of coherence has often been associated with lower levels of social isolation (Chu et al, 2016;Limarutti et al, 2021). Thus, because of their tendency to distance themselves from others, isolated narcissists might be expected to have a less integrated identity.…”
Section: Identity Integration and Social Concordance As Possible Expl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on students' well-being revealed that many experienced loneliness before, during, and after the COVID-19 pandemic, with 29-34% of students reporting high levels of loneliness (Akram et al, 2023;Limarutti et al, 2023;Sivertsen & Johansen, 2022). This sense of loneliness can be enhanced by social exclusion, belittling, and rumours, typical bullying actions among students (Buglass et al, 2021;Cowie & Myers, 2015).…”
Section: Abstract Bystander • Bullying • Social Exclusion • Higher Ed...mentioning
confidence: 99%
“…En la comprensión del constructo de salud, la salutogénesis nos ofrece otra perspectiva, de lo que es la promoción a la salud, la cual está centrada en el sentido de coherencia 18 , sustento teórico que explica el modo en que las personas deben poner en juego su sentido para percibir que son capaces de manejar cualquier situación -independientemente de lo que les esté sucediendo en su vida-y la habilidad para seleccionar el estilo de afrontamiento que mejor se ajuste a la situación dada 19 . En años recientes los constructos bienestar mental, sentido de coherencia y factores sociodemográficos aparecen con mayor frecuencia en publicaciones registradas en bases de datos cuyo objeto de estudio son los estudiantes universitarios, hecho indicativo que dicha asociación es plausible, cobra sentido, es creíble y desde luego sujeto a investigar [20][21][22][23][24] . En México, 25 instituciones de educación superior se reunieron en 2005 para integrar la Red Mexicana de Universidades Promotoras de la Salud 25 con el propósito de establecer bases interinstitucionales de apoyo y colaboración para convertirse en Universidades Saludables.…”
Section: Introductionunclassified